2022
DOI: 10.1002/brb3.2634
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐223‐3p alleviates trigeminal neuropathic pain in the male mouse by targeting MKNK2 and MAPK/ERK signaling

Abstract: Background: Trigeminal neuralgia (TN) is a neuropathic pain that occurs in branches of the trigeminal nerve. MicroRNAs (miRNAs) have been considered key mediators of neuropathic pain. This study was aimed to elucidate the pathophysiological function and mechanisms of miR-223-3p in mouse models of TN. Methods: Infraorbital nerve chronic constriction injury (CCI-ION) was applied in male C57BL/6J mice to establish mouse models of TN. Pain responses were assessed utilizing Von Frey method. The expression of miR-22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Significant downregulation of miR-223-3p has been previously reported in fibromyalgia patients ( Bjersing et al, 2013 ). Furthermore, upregulation of miR-223-3p could alleviate trigeminal neuralgia NP through targeting MKNK2 and MAPK/ERK signals ( Huang et al, 2022 ). In addition, over-expression of miR-223-3p induced by electroacupuncture significantly reduces postherpetic neuralgia pain by inhibiting neuron cell autophagy ( Toyama et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Significant downregulation of miR-223-3p has been previously reported in fibromyalgia patients ( Bjersing et al, 2013 ). Furthermore, upregulation of miR-223-3p could alleviate trigeminal neuralgia NP through targeting MKNK2 and MAPK/ERK signals ( Huang et al, 2022 ). In addition, over-expression of miR-223-3p induced by electroacupuncture significantly reduces postherpetic neuralgia pain by inhibiting neuron cell autophagy ( Toyama et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Encouragingly, limited research has preliminarily revealed the involvement of miR-223-3p in NeP. For example, trigeminal NeP can be alleviated by miR-223-3p targeting MKNK2 and MAPK/ERK signals in male mice ( Huang et al, 2022 ). Another study also reported that electroacupuncture inhibits autophagy in neuronal cells by increasing the expression of miR-223-3p in postherpetic neuralgia ( Zou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-223 overexpression with a lentiviral vector improves the behavioural response to mechanical stimuli and restores MAPKs phosphorylation levels. The effect of miR-223 may occur through the direct interaction with the translational repressor MKNK2, involved in the MAPK pathways [ 42 ].…”
Section: Microrna Involvement In Pain Pathwaysmentioning
confidence: 99%